Studi Analisis Pendapat Husain Syahatah Terhadap Asuransi Syariah Ditinjau Dari Hukum Islam - Sa’diyaturrachma; Aliyah Fitriyanti (LPPM Institut Al-Ma'arif Way Kanan, 2021)
Modern insurance is currently only a business that aims to obtain profits for the welfare of certain parties and is business in nature. In contrast to sharia insurance, it is an effort to protect each other and help each other to face risks through contracts. This study used qualitative research methods. In analyzing the data and taking data sources, the author uses the type of literature review research. The results of the study show that Islamic insurance based on Husain Syahatah's opinion that is good for the community is an Islamic collective insurance system. The Islamic collective insurance contract is a donation contract (tabarru'). Majma' Al-Fiqh Al-Islami has given insurance decisions that are helpful in nature and prohibits commercial or commercial insurance. Husain Syahatah's thoughts also explain the alternative process of applying the concept of insurance